ANALISIS YURIDIS ASAS PERADILAN SEDERHANA CEPAT DAN BIAYA RINGAN DALAM SISTEM PERADILAN PIDANA - Usrin, M (Solusi, 2018)
Purpose of the study: to analyze and describe simple and simple simple justice principles in the criminal justice system. Research Method: This research uses normative juridical method. The result of the research: that the application of simple, quick and light cost principle in the criminal justice can be applied at the time of the examination on the perpetrators of criminal acts committed several crimes (samenloop) by way of merging seseuai with article 18 paragraph (2) Book of Law Criminal law